Improved Extracorporeal Cardiopulmonary Resuscitation (ECPR) Outcomes are Associated with a Restrictive Patient Selection Algorithm - Assouline, Benjamin; Mentha, Nathalie; Wozniak, Hannah; Donner, Viviane; Looyens, Carole; Suppan, Laurent; Larribau, Robert; Banfi, Carlo; Bendjelid, Karim; Giraud, Raphaël (Journal of clinical medicine, 2024)
Introduction: Out-of-hospital cardiac arrest (OHCA) is a leading cause of mortality. Despite decades of intensive research and several technological advancements, survival rates remain low. The integration of extracorporeal cardiopulmonary resuscitation (ECPR) has been recognized as a promising approach in refractory OHCA. However, evidence from recent randomized controlled trials yielded contradictory results, and the criteria for selecting eligible patients are still a subject of debate. Methods: This study is a retrospective analysis of refractory OHCA patients treated with ECPR. All adult patients who received ECPR, according to the hospital algorithm, from 2013 to 2021 were included. Two different algorithms were used during this period. A “permissive” algorithm was used from 2013 to mid-2016. Subsequently, a revised algorithm, more “restrictive”, based on international guidelines, was implemented from mid-2016 to 2021. Key differences between the two algorithms included reducing the no-flow time from less than three minutes to zero minutes (implying that the cardiac arrests must occur in the presence of a witness with immediate CPR initiation), reducing low-flow duration from 100 to 60 min, and lowering the age limit from 65 to 55 years. The aim of this study is to compare these two algorithms (permissive (1) and restrictive (2)) to determine if the use of a restrictive algorithm was associated with higher survival rates. Results: A total of 48 patients were included in this study, with 23 treated under Algorithm 1 and 25 under Algorithm 2. A significant difference in survival rate was observed in favor of the restrictive algorithm (9% vs. 68%, p < 0.05). Moreover, significant differences emerged between algorithms regarding the no-flow time (0 (0–5) vs. 0 (0–0) minutes, p < 0.05). Survivors had a significantly shorter no-flow and low-flow time (0 (0–0) vs. 0 (0–3) minutes, p < 0.01 and 40 (31–53) vs. 60 (45–80) minutes, p < 0.05), respectively. Conclusion: The present study emphasizes that a stricter selection of OHCA patients improves survival rates in ECPR.